Doctors Vision Regarding Undergraduate Medical Curriculum of Bangladesh - Rahman, Md Mohidur; Rahman, Shafiqur; Begum, Noorzahan; Asaduzzaman, AKM; Firoz, Ahmed; Shahjahan, Md; Metul, Morshida Sikder; Nabi, Chawdhury Md Golam (Journal of Bangladesh Society of Physiologist, 2008)
This study was done to identify the lacking in conducting MBBS course-curriculum of Bangladesh. For this purpose a descriptive survey was done among 30 MBBS doctors (Passed within 10 years) of Faridpur district. No internship doctors were included. Self-administered unstructured questionnaire was supplied to them and qualitative analysis of data was done. Majority doctors dissatisfied with (i) Gaining knowledge and skill (ii) Environment of medical colleges (iii) Teaching method (iv) Less MCQ (v) Existing viva-voce (vi) Library facilities (vi) Less clinical symposium. Key Words: Under Graduate; Medical Education; Curriculum; Doctor; Bangladesh DOI:10.3329/jbsp.v2i0.986 J Bangladesh Soc Physiol. 2007 Dec;(2): 54-59.